Acalypha hispida: Chenille Plant - Edward Gilman; Ryan W. Klein; Gail Hansen (EDIS)
This document is about the chenille plant (Acalypha hispida), a vigorous, upright shrub known for its striking red, drooping flowers. It typically grows 5 to 6 feet tall and thrives in USDA hardiness zones 10 through 11. The plant is evergreen, with ovate, medium-green leaves and requires full sun for optimal growth. It is commonly used as an accent, hedge, or container plant due to its long blooming period and ornamental features. The chenille plant is moderately drought-tolerant and performs well in various well-drained soils. It is propagated by cuttings and has no major disease concerns, though pests like scales, mites, and aphids can be problematic in some landscapes. Original publication date October 1999.